Dry land vs still water surfboard paddling: A preliminary investigation. - Volschenk, W.; Crowley-McHattan, Z. J.; Whitting, J. W.; Meir, R. A.; McKenzie, A. K. (Journal of Australian Strength and Conditioning, 2020)
Surfboard paddling is an integral part of surfing, as it is the method used for surfers to catch waves, get to the line-up, and position themselves for wave take-off. Surf coaches and researchers are exploring factors and tools that may help to understand and improve surfboard paddling. One such tool is a swim bench ergometer (SBE). This investigation aimed to determine whether paddling on a SBE had similar neuromechanical demands compared to paddling in a more ecological environment.